Heidegger, Dilthey, and the crisis of historicism - Bambach, Charles R. (Ithaca : Cornell University Press, 1995)
Bambach's account of the demise of historicism within the context of German metaphysics provides a new perspective on the development of Heidegger's concept of ""historicity"" and on the origins of postmodern thought.
Introduction: Modernity and Crisis -- Chapter One. German Philosophy between Scientism and Historicism -- The Legitimation Crisis in Post-Hegelian Philosophy -- The Cartesian Anxiety of Modern Philosophy -- The Cultural Crisis of the German Mandarinate -- Crisis-Consciousness and Cartesian Science -- Chapter Two. Wilhelm Windelband's Taxonomy of the Sciences -- The Neo-Kantian Turn to Questions of Historical Method -- Windelband's Definition of Philosophy as a Science of Values -- The Rectoral Address: "History and Natural Science" -- The European Classification of the Sciences (Plato to Mill) -- Windelband's Aporia: The Logical Problem of Method and the Metaphysical Problem of Freedom -- Chapter Three. Heinrich Rickert's Epistemology of Historical Science -- Rickert's Response to the Contemporary Philosophy of Crisis -- Philosophy as Wissenschaft contra Weltanschauung -- Rickert's Relationship to Kant's Transcendental Idealism -- The Methods of Natural Science and History -- Kulturwissenschaft and Naturwissenschaft -- Values and Objectivity in Historical Science -- Causality and Values: Rickert's Transcendental Philosophy and Friedrich Meinecke's Historicism -- Rickert's Response to the Problems of Historicism -- Rickert's Philosoophy of History -- Chapter Four. Wilhelm Dilthey's Critique of Historical Reason -- Dilthey's Project -- The Unity of the Introduction to the Human Sciences (1883) -- Dilthey's Relationship to Positivism, Idealism, and the Historical School -- The Kantian Fregestellung and Dilthey's "Critique of Historical Reason" -- Dilthey and the Philosophy of Crisis -- Dilthey's Concept of Erlebnis and Its Relation to the Human Sciences -- Historicity and Hermeneutics -- The Crisis of Historical Relativism -- The Antinomy of "Historical" Reason: The Historicity of Truth and the Demand for a Scientific Method -- Chapter Five. "The Time Is Out of Joint": The Young Heidegger's Destruktion of Historicism -- The Revolutionary Language of Theology: Karl Barth's "Epistle to the Romans" -- The Crisis of Faith -- The Situation of University Philosophy -- Heidegger's Practice of Destruktion -- Heidegger's Crisis and the Crisis of Western Thought -- Heidegger's Quarrel with Neo-Kantianism -- Greek Ontology and Christian Kairos: Heidegger's Destruktion of the Metaphysics of Presence -- Dilthey's Fragestellung and Heidegger's Question concerning the Meaning of History -- Historicity and History in Being and Time -- Historicity, Crisis and Decision: Heidegger's Retrieval of Nietzsche -- The Danger of Thinking in a "Time of Need."
Includes bibliographical references (pages 275-287) and index.
Print version record.
JSTOR
Keywords: Heidegger, Martin, -- 1889-1976.; Dilthey, Wilhelm, -- 1833-1911.; Dilthey, Wilhelm, -- 1833-1911.; Heidegger, Martin, -- 1889-1976.; Heidegger, Martin, -- 1889-1976 -- Et l'historicisme.; Dilthey, Wilhelm, -- 1833-1911 -- Et l'historicisme.; Windelband, W. -- 1848-1915.; Rickert, Heinrich, -- 1863-1936.; Dilthey, Wilhelm, -- 1833-1911; Heidegger, Martin, -- 1889-1976; Dilthey, Wilhelm -- 1833-1911; Heidegger, Martin -- 1889-1976; Rickert, Heinrich -- 1863-1936; Windelband, Wilhelm -- 1848-1915; Heidegger, Martin; Dilthey, Wilhelm; Historicism; Philosophy, German -- 19th century; Philosophy, German -- 20th century; Historicisme; Philosophie allemande -- 19e siècle.; Philosophie allemande -- 20e siècle.; historicism (theory); HISTORY -- Historiography; Historicism; Philosophy, German; Historismus; Historizismus; Krise; Historisme; 1800-1999